Rupture Model for the 29 July 2021 MW 8.2 Chignik, Alaska Earthquake Constrained by Seismic, Geodetic, and Tsunami Observations. Issue 7 (10th July 2022) - Ye, Lingling; Bai, Yefei; Si, Daojun; Lay, Thorne; Cheung, Kwok Fai; Kanamori, Hiroo
Abstract: A great earthquake struck the Semidi segment of the plate boundary along the Alaska Peninsula on 29 July 2021, re‐rupturing part of the 1938 rupture zone. The 2021 M W 8.2 Chignik earthquake occurred just northeast of the 22 July 2020 M W 7.8 Simeonof earthquake, with little slip overlap. Analysis of teleseismic P and SH waves, regional Global Navigation Satellite System (GNSS) displacements, and near‐field and far‐field tsunami observations provides a good resolution of the 2021 rupture process. During ∼60‐s long faulting, the slip was nonuniformly distributed along the megathrust over depths from 32 to 40 km, with up to ∼12.9‐m slip in an ∼170‐km‐long patch. The 40–45 km down‐dip limit of slip is well constrained by GNSS observations along the Alaska Peninsula. Tsunami observations preclude significant slip from extending to depths <25 km, confining all coseismic slip to beneath the shallow continental shelf. Most aftershocks locate seaward of the large‐slip zones, with a concentration of activity up‐dip of the deeper southwestern slip zone. Some localized aftershock patches locate beneath the continental slope. The surface‐wave magnitude M S of 8.1 for the 2021 earthquake is smaller than M S = 8.3–8.4 for the 1938 event. Seismic and tsunami data indicate that slip in 1938 was concentrated in the eastern region of its aftershock zone, extending beyond the Semidi Islands, where the 2021 event did not rupture. Plain Language Summary: The Pacific plate underthrusts the North American plate along the Alaska‐Aleutian subduction zone producing great earthquakes along most of the plate boundary. The region, that ruptured in 1938, hosted another great earthquake with magnitude 8.2 on 29 July 2021 offshore of Chignik, adjacent to a magnitude 7.8 event in 2020 beneath the Shumagin Islands. Using seismic wave recordings, Global Navigation Satellite System static displacements, and tsunami wave recordings at regional and distant locations, we determine the space‐time evolution of slip during the 2021 rupture process. The rupture extended northeastward ∼170 km, ending just short of the Semidi Islands. The slip is concentrated on the megathrust, from 32‐km to 40‐km deep. Shallow slip at depths <25 km is precluded by the tsunami observations, confining all rupture to beneath the shallow continental shelf. Most aftershocks are up‐dip of the large‐slip regions with a concentration in the shallow region of the southwestern rupture zone. Comparisons of observations and rupture models with the 1938 event indicate distinct slip distributions and seismic energy release, with the 1938 event being somewhat larger and extending further northeast than the 2021 rupture. This provides strong evidence that the 2021 event is not a simple repeat failure of the 1938 rupture. Key Points: The slip distribution of the 2021 Chignik M W 8.2 earthquake is constrained by joint analysis of seismic, geodetic, and tsunami recordings During the ∼60‐s long rupture, patchy slip of up to 12.9 m occurred at depths of 32–40 km on the megathrust below the continental shelf The 2021 slip pattern differs from the 1938 M W 8.2 rupture, with larger slip in the west and no slip in the easternmost 1938 rupture zone